2017
DOI: 10.1002/dac.3339
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating intrusion prevention systems with evasions

Abstract: Intrusion prevention systems have become a common security measure in the past 20 years. Their promise is the possibility to prevent known attacks against vulnerable, unpatched devices inside enterprise networks. However, evasion techniques that enable the attacker to evade the eye of the intrusion prevention system are a potential problem for this capability. These techniques take advantage of the robustness principle that has guided designers to create systems that will try to recreate protocol content from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Vidal et al [6] classified the most representative evasion techniques into five categories: Insertion and Evasion, Denial of Service, Malware Obfuscation, Link Layer, and Application Layer. A single evasion technique is called an atomic evasion [7]. Xiong et al [8] summarized common atomic evasion techniques and at least 147 atomic evasions have been discovered [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vidal et al [6] classified the most representative evasion techniques into five categories: Insertion and Evasion, Denial of Service, Malware Obfuscation, Link Layer, and Application Layer. A single evasion technique is called an atomic evasion [7]. Xiong et al [8] summarized common atomic evasion techniques and at least 147 atomic evasions have been discovered [9].…”
Section: Introductionmentioning
confidence: 99%
“…Modern NIDS vendors publish extensive performance testing results regarding the line speed and breadth of attacks detected by their systems, but little information regarding their resilience to evasions. A recent effectiveness evaluation of 35 well-known evasions against nine commercial and one free state-of-the-art NIDS showed that even a single evasion technique from the 1990s with suitable parameters can successfully evade the detection of the best existing NIDS [7]. Cheng et al [11] assessed the effectiveness of evasion techniques for FortiGate, Snort and ZyXEL.…”
Section: Introductionmentioning
confidence: 99%